EKSISTENSI PERPUSTAKAAN PERGURUAN TINGGI DALAM MEWUJUDKAN MASYARAKAT INFORMASI MENUJU KAMPUS SAINS ISLAM REFLEKSI SURAU MINANGKABAU - Sri Wahyuni; Zafirah Quroatun ‘Uyun, (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2022)
The purpose of this study is to describe the existence of a university library in creating an information society towards the Islamic Science Campus of Reflection at Surau Minangkabau. In this study, the researcher used a qualitative descriptive type of research. Data collection techniques through observation, interviews and documentation. The results of the study indicate that the role of the university library is to become an incubation center and research innovation center that serves as an intermediary and seeks to bridge the information explosion, so that information can be spread comprehensively and can be utilized by the information community, in this case the academic community. UIN Mahmud Yunus Batusangkar has the tagline